Isu pendidikan luar bandar di Perak - Kasa Zakaria, Dawi Amir Hasan, Wahid Azhar, Madon Mohd Sani, Idris Mohd Noor, Ali Shaharudin (Universiti Pendidikan Sultan Idris, 2010)
Isu pendidikan luar bandar di Perak by Kasa Zakaria, Dawi Amir Hasan, Wahid Azhar, Madon Mohd Sani, Idris Mohd Noor, Ali Shaharudin,